Teaching and Learning English Vocabulary - Červinková, Šárka (Univerzita Pardubice, 2013)
The diploma thesis is devoted to teaching and learning English vocabulary. At first, the theoretical part explains the acquisition and learning vocabulary. Then it describes vocabulary from the linguistic and didactic point view and emphasizes its essential parts to be included when teaching and learning vocabulary. Moreover, the thesis deals with factors which influence the selection of vocabulary and the development of teaching methods, traditional as well as alternative, which can be used when teaching and learning English vocabulary. The main focus is paid to individual phases of teaching and learning vocabulary including presentation and practice techniques which are followed by teaching and learning vocabulary strategies. The last chapter of the theoretical part provides the analysis of learning styles with the focus on visual, auditory and kinaesthetic/tactile type. The practical part then deals with the research carried out with the chosen groups of lower secondary learners and their teachers. The aim of the research is to find out which techniques and activities teachers use when presenting and practicing English vocabulary and if they consider the individual learning styles.
Výuka anglické slovní zásoby
Keywords: výuka slovní zásoby; učení se slovní zásoby; osvojování jazyka; presentační techniky; procvičovací techniky; styly učení; visuální; auditivní; kinestetický; taktilní; teaching vocabulary; learning vocabulary; acquisition; presentation techniques; practice techniques; learning styles; visual; auditory; kinaesthetic; tactile